Remarkable transitions of yield behavior and Lüders deformation in pure Cu by changing grain sizes. (1st January 2018) - Tian, Y.Z.; Gao, S.; Zhao, L.J.; Lu, S.; Pippan, R.; Zhang, Z.F.; Tsuji, N.
Abstract: Fully recrystallized ultrafine-grained (UFG) pure Cu specimens were fabricated by high-pressure torsion (HPT) and controlled annealing. The recrystallized UFG Cu with a minimum mean grain size of 0.51 μm showed high yield strength, good ductility, obvious yield drop and large Lüders strain during tensile test. The mechanical behavior of the Cu specimen became sensitive to the change in the grain size from 0.2 μm to 4.2 μm. The continuous transitions of yield behavior and Lüders deformation with grain sizes were discussed. Graphical abstract: